2017
DOI: 10.1016/j.addbeh.2016.08.044
|View full text |Cite
|
Sign up to set email alerts
|

PTSD, alcohol dependence, and conduct problems: Distinct pathways via lability and disinhibition

Abstract: This study tested the role of affect lability and disinhibition in mediating associations between PTSD symptoms and two forms of alcohol-related problems, dependence syndrome symptoms (e.g., impaired control over consumption) and conduct problems (e.g., assault, risk behaviors). Genotype at the serotonin transporter linked polymorphic region (5-HTTLPR) was hypothesized to moderate associations between traumatic stress and PTSD symptoms. In addition, the study tested whether childhood traumatic stress moderated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 72 publications
3
26
1
Order By: Relevance
“…In this regard, exacerbations in PTSS may result in dyscontrolled drinking characteristic of dependence syndrome and contribute to a wide variety of conduct related problems (e.g., interpersonal conflict) that can occur independent of drinking level. This perspective is consistent with between-subjects research indicating that associations between PTSD and alcohol-related problems are mediated by both affect and behavioral dysregulation (Miller, Vogt, Mozley, Kaloupek, & Keane, 2006; Read, Merrill, Griffin, Bachrach, & Khan, 2014; Simons et al, 2017). This suggests that the functional association extends beyond coping with negative affect and symptoms and that there are two distinct pathways linking PTSD and alcohol related problems.…”
Section: Ptsd and Alcohol Use: Functional Associationssupporting
confidence: 89%
See 2 more Smart Citations
“…In this regard, exacerbations in PTSS may result in dyscontrolled drinking characteristic of dependence syndrome and contribute to a wide variety of conduct related problems (e.g., interpersonal conflict) that can occur independent of drinking level. This perspective is consistent with between-subjects research indicating that associations between PTSD and alcohol-related problems are mediated by both affect and behavioral dysregulation (Miller, Vogt, Mozley, Kaloupek, & Keane, 2006; Read, Merrill, Griffin, Bachrach, & Khan, 2014; Simons et al, 2017). This suggests that the functional association extends beyond coping with negative affect and symptoms and that there are two distinct pathways linking PTSD and alcohol related problems.…”
Section: Ptsd and Alcohol Use: Functional Associationssupporting
confidence: 89%
“…In this regard, the autoregressive parameter may be conceptualized as the manifestation of the latent alcohol use disorder itself. Consistent with previous research and theory, we anticipated that affect lability effects would be more pronounced in the dependence syndrome relative to conduct problems model (McCarthy et al, 2010; Simons et al, 2017).…”
Section: Current Studysupporting
confidence: 61%
See 1 more Smart Citation
“…Thus, the S allele of 5-HTTLPR may increase the risk for ODD, whilst the L allele may be protective. These results are consistent with previous reports showing that the S allele was associated with violent suicide [ 30 ] and violence, ADHD [ 31 ], PTSD, alcohol dependence, and conduct problems [ 32 ], but not with personality traits [ 33 ]. However, a study showed that the L allele of 5-HTTLPR might increase the risk of attacking behaviors in the Alzheimer’s patients [ 34 ], which is contrary to our findings.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, it is possible that depression, PTSD, and insomnia operate through one another in such a way that independent effects are attenuated when all symptoms are included in the model. Alternatively, it is possible that rates of clinically significant PTSD were too low in this sample to establish direct associations between PTSD symptoms and alcohol-related outcomes, as a number of studies linking PTSD symptoms to alcohol outcomes included clinician-administered assessments of PTSD and/or larger proportions of participants who met criteria for PTSD (Fuehrlein et al, 2014; McDevitt-Murphy et al, 2015; Simons et al, 2017). …”
Section: Methodsmentioning
confidence: 99%